SUSTAINABLE PRODUCTIVE WAQF MANAGEMENT OF MANARUL ILMI ITS FOUNDATION PERSPECTIVE OF MAQÂSHID SHARIA - Pratama, Roby Julio; Wahab, Abdul; Berkah, Dian (istinbath, 2025)
This research project aims to examine the management of sustainable productive waqf at the Manarul Ilmi ITS Foundation and assess its suitability from a Maqâshid Syariah perspective. It used a qualitative case study approach. Data were collected through interviews with foundation administrators (nazhir), waqf fund managers, and donors (waqif). Additionally, the researchers conducted direct observations of the waqf business unit and analysed supporting documents, such as programmes and financial reports. The results showed that the management of productive waqf at the Manarul Ilmi Foundation includes asset development in the form of waqf funds from alums and benefactors, as well as thematic programmes such as well waqf, mosque design waqf, and scholarships. However, the sustainability aspect has not yet been fully incorporated into long-term strategic planning or social impact measurement. From a Maqâshid Syariah perspective, this management fulfils several aspects, such as hifz al-din (through mosque utilisation and da'wah), hifz al-'aql (through scholarship waqf), and hifz al-nafs (through well waqf). However, the hifz al-mal aspect still requires improvement in efficiency, transparency, and reinvestment of waqf proceeds. This research recommends that foundations develop a productive waqf governance system based on sharia maqâshid indicators, strengthening public engagement and institutional documentation to ensure the long-term benefits of the waqf.